Neoadjuvant immunotherapy for colorectal cancer: Right regimens, right patients, right directions? - Zhu, Jiahao; Lian, Jie; Xu, Benjie; Pang, Xiangyi; Ji, Shengjun; Zhao, Yutian; Lu, Haibo (Frontiers in Immunology, 2023)
Neoadjuvant chemoradiotherapy (NACRT) or chemotherapy (NACT) followed by radical resection and then adjuvant therapy is considered the optimal treatment model for locally advanced colorectal cancer (LACRC). A recent total neoadjuvant therapy (TNT) strategy further improved the tumour regression rate preoperatively and reduced local-regional recurrence in locally advanced rectal cancer (LARC). However, distant metastasis was still high, and little overall survival benefit was obtained from these preoperative treatment models. According to mismatch repair protein expression, MSI-H/dMMR and non-MSI-H/pMMR statuses were defined in colorectal cancer (CRC) patients. Due to the special features of biologics in MSI-H/dMMR CRC patients, this subgroup of patients achieved little treatment efficacy from chemoradiotherapy but benefited from immune checkpoint inhibitors (ICIs). The KEYNOTE-177 trial observed favourable survival outcomes in metastatic CRC patients treated with one-line pembrolizumab with tolerable toxicity. Given the better systemic immune function, increased antigenic exposure, and improved long-term memory induction before surgery, neoadjuvant ICI (NAICI) treatment was proposed. The NICHE trial pioneered the use of NAICI treatment in LACRC, and recent reports from several phase II studies demonstrated satisfactory tumour downsizing in CRC. Preclinical rationales and preliminary early-phase human trials reveal the feasibility of NAICI therapy and the therapeutic efficacy provided by this treatment model. Better tumour regression before surgery also increases the possibility of organ preservation for low LARC. However, the optimal treatment strategy and effective biomarker identification for beneficiary selection remain unknown, and potential pitfalls exist, including tumour progression during neoadjuvant treatment due to drug resistance and surgery delay. Given these foundations and questions, further phase II or III trials with large samples need to be conducted to explore the right regimens for the right patients.